Characterization of new plant type core set of rice (Oryza sativa L.) using QTL/gene-linked markers - B, Rachana; KB, Eswari; B, Jyothi; G, Lakshmi Devi; LRK, Jai Vidhya; P, Laxmi Bhavani; M, Bharath; P, Raghuveer Rao; J, Aravind Kumar; R, Fiyaz Abdul; CN, Neeraja; LV, Subba Rao; et al. (ORYZA-An International Journal of Rice, 2019)
Genetic diversity in New Plant Type core set of rice was studied at molecular level employing 52 yield relatedÂ and 12 randomly chosen markers. 42 markers were polymorphic among the genotypes with a total of 84 alleles.Â The number of alleles per locus ranged from 2 to 4 with an average of 3.0 per locus. The PIC value ranged fromÂ 0.07 to 0.51 with an average of 0.31. Gene specific markers (SCM2-indel2, Gn1a-indel3, TGW6-1d and GS5-Â 03SNP), functional genes (Ghd7-sel and DEP1-promoter), linked markers RM8080 and RM340 were found toÂ be the most appropriate marker to discriminate among the rice genotypes owing to the highest PIC value ofÂ more than 0.5. The cluster analysis distinguished these accessions in to eight clusters based on the principle of Unweighted Pair Wise Method using Arithemetic Average (UPGMA) constructed by Jaccard’s similarityÂ Coefficient. The dendrogram showed that the genotypes with common phylogeny and geographical orientationÂ tend to cluster together. The highest similarity coefficient value was observed between the IRGC 25510 andÂ IRGC 10658 (0.67) whereas lowest value was observed for Swarnadhan (0.18) and Azucena (0.21), showingÂ highly diverse genotypes. Thus, these accessions were genetically diverse and could be directly utilized in hybridization programme for improvement of yield and related traits.